2018
DOI: 10.1037/npe0000086
|View full text |Cite
|
Sign up to set email alerts
|

A critical comparison of selected implicit measurement methods.

Abstract: Indirect, implicit measurement methods facilitate access to individual unconscious mental processes. In recent years, these methods have become more popular and are now broadly used in personality and social psychology. Approximately 20 implicit measurement methods have been developed, and new ones are being introduced continuously. So far, research on indirect measuring methods has focused on the development of new methods as well as improving existing ones. However, different methods have different strengths… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 76 publications
0
14
0
Order By: Relevance
“…The Affective Misattribution Procedure (AMP) has gained popularity, and it arguably produces more stable and more genuine (less able to be faked) results than the IAT due to not relying on response times (Znanewitz et al, 2018). The AMP compares the valence of responses to a neutral stimulus (e.g., ambiguous Chinese character) after being primed-typically-with various images.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Affective Misattribution Procedure (AMP) has gained popularity, and it arguably produces more stable and more genuine (less able to be faked) results than the IAT due to not relying on response times (Znanewitz et al, 2018). The AMP compares the valence of responses to a neutral stimulus (e.g., ambiguous Chinese character) after being primed-typically-with various images.…”
Section: Discussionmentioning
confidence: 99%
“…The IAT is not the only test of implicit measures, but it is known for its comparatively high reliability and validity and it generally has superior psychometrics in direct comparisons with other measures (Bar-Anan & Nosek, 2014). Though some scholars debate the interpretability of the IAT effect or construct (e.g., Mierke & Klauer, 2001), and concern exists over the ability of experienced IAT users to manipulate its effects (Fiedler & Bluemke, 2005), the IAT continues to be applied to a growing number of topics, and it typically adds predictive validity above and beyond that which self-report measures offer (Greenwald et al, 2009;Znanewitz et al, 2018).…”
Section: The Implicit Association Test (Iat)mentioning
confidence: 99%
“…Although the (md)-IAT was criticized regarding its capability of testing and correctly classifying attitudes and stereotypes (Fiedler et al, 2006), it is well suitable for the present research question of revealing automatic, perceptive associations of attributes to what is stored in the perceivers mind. Furthermore, other methods of measuring implicit (automatic) associations and attitudes (e.g., affective priming) seem to be neither necessarily superior to the (md)-IAT in terms of psychometric criteria (Znanewitz et al, 2018), nor to be the better choice for the present research question, as we are interested in differences in associations across dimensions.…”
Section: Introductionmentioning
confidence: 94%
“…conscious parts of the brain, as opposed to intrinsic ones, i.e. non-conscious parts (Shah et al, 2016;Znanewitz et al, 2018). It was found that consumers do not have the tacit knowledge to evaluate all the intrinsic cues that surround a product bundle.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In line with recent methodological advances from the behavioral economics and social psychology literature, researchers in the field of consumer behavior are trying in addressing the conscious and nonconscious shopping behavior of consumers, attitude formation, and behavioral judgment responses (Dimofte, 2010;Znanewitz et al, 2018). It can be argued that consumers are not always seeking absolute maximization over their choices, and they do not interpret the information presented on the decision tasks in terms of perceived positive or negative outcomes, like gains and losses (Van Osselaer, 2012;Babutsidze, 2007;McGraw et al, 2010;Jacoby et al, 1994;Stampfl, 1978;Chung -Hoon and Young-Gul, 2003;Holt, 1995).…”
Section: Introductionmentioning
confidence: 99%